Soft Robot Kinematic Control Via Manipulability-Aware Redundancy Resolution - Azizkhani, Milad; Ha, Junhyoung; Gunderman, Anthony L.; Chen, Yue (American Society of Mechanical Engineers, 2025)
This article addresses the kinematic control of a redundant soft robotic arm. Full pose kinematic control of soft robots is challenging because direct application of the classical controllers developed based on rigid robots to soft robots could lead to unreliable or infeasible motions. In this study, we explore the manipulability property of a soft robotic arm and develop an advanced resolved-rate controller that prioritizes position over orientation control and switches its modes and gains based on position and orientation manipulabilities, enabling stable motion even when the robot is close to the singular configurations. The simulation and experimental results indicate that our proposed method outperforms previous methods in terms of both accuracy and smoothness during operation.